Pengakuan, Pengukuran, Dan Penyajian Aset Biologis pada PT. XYZ (Peternakan Sapi) - Lutfi Bimantoro; Irawan Irawan; Destia Pentiana (Jurnal Ilmiah ESAI, 2020)
Final Project Report aims to explain whether the recognition, measurement and presentation of biological assets at PT XYZ is in accordance with the accounting standards set by PSAK No. 69. The source of data for writing this final project report is secondary data using the documentation data collection method. The data analysis method used by the author in preparing the final project report is a descriptive method with a quantitative approach. The author discusses the recognition, measurement, and presentation of biological assets at PT. XYZ whether it is in accordance with accounting standards in force in Indonesia, namely PSAK No.69. There are differences in recognition, measurement and presentation according to PT. XYZ and PSAK No.69 must be adjusted.